Toward understanding and enhancing self-determination: a qualitative exploration with autistic adults without co-occurring intellectual disability - Thompson-Hodgetts, Sandy; Ryan, Jacalyn; Coombs, Emily; Brown, Heather M.; Xavier, Adrian; Devlin, Christina; Lee, Austin; Kedmy, Adam; Borden, Anne (Frontiers in Psychiatry, 2023)
Introduction: Self-determination is a fundamental human right positively related to quality of life. However, Autistic people are reported to be less self-determined than non-autistic people. We aimed to (1) understand what self-determination means to Autistic people from their perspective, (2) explore their perceptions of current barriers to being self-determined, and (3) learn from Autistic people about how they would like to be supported to be self-determined. Methods: Semi-structured interviews were done with 19 Autistic adults without co-occurring intellectual disability. Data were analyzed by three Autistic and two non-autistic researchers through an iterative process of data familiarization, coding, and theme development, informed by reflexive thematic analysis. Autistic Community Partners (ACP) were also engaged throughout the study, and provided substantive feedback on all methods and results. Results: Self-determination held the same meaning for Autistic people as non-autistic people. More specifically, participants discussed having the opportunity and support to make choices and decisions in life without unnecessary control from others. Experiences of self-determination were centred around: (1) lack of opportunity, influenced by ableist expectations and discrimination, and (2) executive processing differences that interfered with choice and decision-making. Desired areas of support related to providing opportunities to (1) make choices and exert autonomy, (2) be supported to unmask and be valued as one’s authentic Autistic self, and (3) offering pragmatic support for executive processing differences. Conclusions: Autistic adults desire to be self-determined and can flourish with support, as they determine to be appropriate, which might look different from support commonly offered or sought by non-autistic people. Although individualized support was discussed, the ideal desired support was for an inclusive society that values and respects their neurodivergence, rather than imposing ableist expectations. An inclusive society is only achievable through reduced (or eliminated) stigma and prejudice against Autistic people.